Enhancing photocatalytic activity of titanium dioxide through incorporation of MIL‐53(Fe) toward degradation of organic dye - Nurul Wafa Othman; Hasmira Radde; Perng, Yang Puah; Yee, Soon Ling; Pak, Yan Moh (2018)
Photocatalytic activity of titanium(IV) oxide (TiO2) can be enhanced through modification of its surface‐active sites. Here, iron(III) carboxylate [MIL‐53[Fe]]‐incorporated TiO2 (as MIL‐53(Fe)/TiO2) was prepared using a hydrothermal method. This material was then calcined at 500°C to obtain a MIL‐53(Fe)‐derived γ‐Fe2O3/TiO2 photocatalyst. A photocatalytic study of MIL‐53(Fe)/TiO2 and MIL‐53(Fe)‐derived γ‐Fe2O3/TiO2 toward cationic methylene blue (MB) and anionic methyl orange (MO) showed that MIL‐53(Fe)/TiO2 (0.25 wt%) and MIL‐53(Fe)‐derived γ‐Fe2O3/TiO2 (0.75 wt%) resulted the best degree of dye degradation. The MIL‐53(Fe)‐derived γ‐Fe2O3/TiO2 (0.75 wt%) composite for instance is capable of degrading almost 100% of 20‐ppm MB and MO, respectively, within 6 hr. Photocatalytic degradation of MB and MO was well fitted to the Langmuir‐Hinshelwood pseudo‐first order kinetics model, which indicates physisorption as the key partway that facilitates dye decomposition on the surface of a photocatalyst under UV‐A irradiation. This study provides new insights into the exploration of MILs/TiO2 materials for the environmental remediation and pollution control.